Fodder quality and yields of cowpea (Vigna unguiculata) as affected by tillage practices and nitrogen management options - kandhar, Mallikarjun (Indian Journal of Animal Nutrition, 2018)
Quality of fodder crops depend on better crop growth and developmentÂ  which is affected by agronomic practices such as tillage practices and nitrogen management, to studyÂ  this Â an experiment was conducted Â in a split plot design at ICAR-NDRI Karnal â€œPerformance of fodder cowpea under different tillage and nitrogen management practicesâ€ consist of three contrasting tillage practices as main plots zero tillage (ZT), conventional tillage (CT) and raised bed (RB) andÂ  six nitrogen management as sub plot treatments 0%N, 75%N, 75%N+Rhizobium,100%N, 100%N+RhizobiumÂ  and 125%N. The experiment site was neutral in reaction, low available N and medium in P and K. After harvest representative samples grounded and analysed for different fodder quality parameters. Among tillage practices significantly higher DMY and lower T-CHO recorded in RB over but RB was statistically on par with ZT. In nitrogen management options significantly higher DMY recorded in 125%N over 75%Nand 0%Nbut 125%Nwas on par with 100%N+Rhizobium, 100%N and 75%N+Rhizobium. While significantly higher value of DM, TA, CP and lower value of NDICP (DM %), cell content, T-CHO, NDF and cellulose content were recorded in 125% N over 100%N, 75%+Rhizobium,75%Nand 0%N but 125%Nwas statically on par with 100%N+Rhizobium. However significantly lower values of NDICP (CP %), ADICP (DM % and CP %), ADF and hemicellulose content were also observed in 125%N over 75%N+Rhizobium, 75%N and 0%N but 125%N was statistically on par with 100%N and 100%N+Rhizobium.Therefore combination of ZT/RB with 100%N+Rhizbium for effective yield and quality parameters of fodder cowpea.